The Relationship Between Socioeconomic Status And Nutritional Status Of Toddlers In Buha Village Mapanget Sub-District Manado City (Literature Review) - Tarigan, Herdianta; Mulia Saragih, Varellisia Sandjeri; Lumbantoruan, Helmalia; Pasaribu, Riris; Sianipar, Juni; Situmeang, Exaudya (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Nutritional status is the state of the body as a result of food consumption and nutrient use. Nutritional status is influenced by several factors, one of which is socioeconomic level. Children under five years old (toddlers) are the "golden age" in growth and development. Toddlers are the age group that most often suffers from malnutrition. Malnourished toddlers can be caused by family socioeconomic factors. Socioeconomic status as the root of malnutrition related to the purchasing power of food in households has an impact on the fulfillment of nutrients. The purpose of the study was to determine the relationship between socioeconomic status and nutritional status of toddlers in Buha Village, Mapanget District, Manado City. The research method is analytical with a cross sectional approach. The samples used were 71 toddlers using purposive sampling techniques. The data collection process uses questionnaires and is statistically tested with percentage formulas to answer the first and second statements, Spearmen Correlation tests to answer the third statement. The results of the study found that the picture of socioeconomic status is low income, the picture of nutritional status of toddlers is more nutrition and there is no significant relationship between socioeconomic status and nutritional status of toddlers with a value of p = 0.60>0.05. It can be concluded that there is no significant relationship between socioeconomic status and nutritional status of toddlers in Buha Village, Mapanget District, Manado City. Recommendations for further researchers to add other variables, namely factors that affect the nutritional status of toddlers, namely hygiene, environmental sanitation, where poor environmental conditions allow various diseases to occur, including malnutrition and even malnutrition.